Perioperative outcome between open renal stone-removal surgery and PCNL in patients with staghorn stones - Gede Wirya Kusuma Duarsa (Journal of Global Pharma Technology, 2019)
Background: Percutaneous nephrolithotomy (PCNL) has become the treatment of choice for staghorn stones, replacing open stone surgery. However, in a developing country, open stone surgery is still the treatment of choice due to its nature for not requiring endourology devices, it can be performed by a general surgeon, and it is financially acceptable.Objective: This study aims to compare the cost-related outcome between PCNL and open renal stone surgery in patients with staghorn stones.Method: Data were collected retrospectively, taken from patients’ medical records who underwent PCNL and open stone surgery in three hospitals from 2016-2017. Seventy-eight patients were divided equally into PCNL group and open surgery group. Data of the hospital length of stay, the volume of blood loss during surgery, stone-free rate, and post-operative additional procedures were recorded.Outcome Measurements and Statistical Analysis: The data were analyzed using SPSS version 23.0 for Windows.Results: The hospital length of stay was shorter in PCNL compared to open stone surgery (3 vs. 4 days, p<0.001). The post-operative stone-free rate was lower in PCNL compared to open stone surgery (48.7 vs. 92.3%, p<0.001). More post-operative additional procedures were found in PCNL compared to open stone surgery (p<0.001). There was no significant difference in the amount of blood loss during surgery in both groups (p=0.102).Conclusions: PCNL is a minimally invasive procedure that is effective and safe for treating staghorn stones. Nevertheless, in places where PCNL is unavailable, open stone surgery can still be a choice for treatment.